On Multiple Belonging: Engaging Human Rights from a Buddhist-Christian, and Feminist Liberative Praxis - Pontoriero, Eleanor (Buddhist Christian studies, 2019)
This is an expanded version of a paper presented at the Parliament of World Religions, November 2018, Toronto, Canada., Dedicated to the memory of our little sister, Jakelin Caal Maquin, a seven-year-old Indigenous migrant girl from Guatemala who died on December 8, 2018, after being detained in a US border cell, and to all our sisters North and South, may they be free from want, fear, and oppression., My article explores multiple belonging in the contemporary world with a focus on feminist liberative praxis, Buddhist and Christian, addressing the human rights of women and girls. My aim is not to compare and contrast each religious tradition point by point. Rather, I explore the parameters of multiple belonging traversing religious and secular spheres. As a feminist, and Buddhist practitioner, my gender, ethnicity, and social background have not been without challenges. Multiple belonging informs how I practice, teach, and engage human rights and peacebuilding across difference, and through an intersectional lens. The resonant theme in my article is the inextricable link between the spiritual, political, and personal pursuit of liberation. Article 29 of the United Nations Declaration of Human Rights enjoins us to exercise our moral responsibility to the global community by virtue of our birthright into the human family. This responsibility extends to all sentient and non-sentient life. Religious and secular resources may be mutually supportive in this endeavor. Thus multiple belonging addresses our interdependence as a global community.